Descendants of the first stars: the distinct chemical signature of second-generation stars - Hartwig, Tilman; Yoshida, Naoki; Magg, Mattis; Frebel, Anna; Glover, Simon; Gómez, Facundo A.; Griffen, Brendan; Ishigaki, Miho N.; Ji, Alexander P.; Klessen, Ralf S.; O’Shea, Brian W.; Tominaga, Nozomu (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Extremely metal-poor (EMP) stars in the Milky Way (MW) allow us to infer the properties of their progenitors by comparing their chemical composition
Gesehen am 16.10.2019